Hubungan antara Penggunaan Media Sosial Twitter dengan Keterbukaan Diri Mahasiswa - Dhita Fahira; Neni Yulianita (Bandung Conference Series: Public Relations, 2022)
Abstract. The development of technology and information has developed rapidly. The things that arise from its development have a considerable impact on life.Technological advances have also given birth to various forms of new media or can be called new media in establishing internet-based communications, computers, and various other forms of social networking. The development of technology and information has developed rapidly. The things that arise from its development have a considerable impact on life.Technological advances have also given birth to various forms of new media or can be called new media in establishing internet-based communications, computers, and various other forms of social networking. Twitter has features that can appeal to its users, such as features for mentions, direct messages, latest news, trending and others. The average content on Twitter tends to upload users sharing their stories, activities, and personal opinions with selected people or followers of these users. With the social media twitter allows its users to be more open about themselves. Therefore, the researcher was interested in conducting a research entitled, "Hubungan Penggunaan Media Sosial Twitter dengan Keterbukaan Diri Mahasiswa". The purpose of this study was to analyze how big the relationship between Twitter social media usage and student self-disclosure. The method used in this research is a quantitative method with a correlational study approach. The data collection technique was carried out by distributing questionnaires to 94 students of Fikom Unisba class of 2017-class of 2020 using simple random sampling technique. The analysys tehcnique used is descriptive analysys. The results of this study are that there is a strong relationship between the use of social media twitter with student self-disclosure. Abstrak. Perkembangan teknologi dan informasi telah berkembang dengan pesat. Hal yang ditimbulkan dari perkembangannya memberikan dampak yang cukup besar terhadap kehidupan masyarakat luas.Dari kemajuan teknologi juga melahirkan beraneka ragam bentuk media baru atau dapat disebut dengan new media dalam melangsungkan komunikasi yang berbasis internet, komputer, dan beragam bentuk jejaring sosial lainnya. Dari sekian banyak media sosial, twitter menjadi salah satu yang memiliki banyak peminat. Twitter mempunyai fitur-fitur yang dapat memberikan daya tarik kepada para penggunanya seperti fitur mention, direct message, latest news, trending dan lain-lain. Rata-rata isi dalam twitter cenderung untuk mengunggah penggunanya berbagi cerita, aktivitas, dan opini pribadinya kepada orang-orang pilihan atau pengikut dari pengguna tersebut. Dengan adanya situs media sosial twitter memungkinkan para penggunanya untuk menjadi lebih terbuka mengenai dirinya sendiri. Maka dari itu, peneliti merasa tertarik untuk melakukan penelitian yang berjudul "Hubungan Penggunaan Media Sosial Twitter dengan Keterbukaan Diri Mahasiswa. Tujuan penelitian ini adalah untuk menganalisis seberapa besar hubungan penggunaan media sosial twitter dengan keterbukaan diri mahasiswa. Metode yang digunakan dalam penelitian ini adalah metode kuantitatif dengan pendekatan studi korelasional. Teknik pengumpulan data dilakukan dengan menyebarkan angket/kuesioner kepada 94 mahasiswa Fikom Unisba angkatan 2017-angkatan 2020 dengan menggunakan Teknik simple random sampling. Adapun teknik analisis yang digunakan ialah analisis deskriptif. Hasil dalam penelitian ini adalah terdapat hubungan yang kuat antara penggunaan media sosial twitter dengan keterbukaan diri mahasiswa.